2022
DOI: 10.1161/hypertensionaha.122.19256
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, Arterial Stiffness, and Diabetes: a Prospective Cohort Study

Abstract: Background: Whether the combination of different blood pressure and arterial stiffness (AS) status is independently associated with diabetes has not been fully investigated so far. This study aimed at investigating the status of hypertension and AS in determining diabetes. Methods: This prospective cohort study included 11 156 participants from the Kailuan study. AS was measured by brachial-ankle pulse wave velocity. We compared the risk of diabetes bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 47 publications
0
53
0
1
Order By: Relevance
“…A previous study investigated the significance of combined evaluation of arterial stiffness and hypertension status on diabetes onset [ 18 ]. The Framingham offspring cohort study found the relative contributions of arterial stiffness and hypertension to cardiovascular diseases [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study investigated the significance of combined evaluation of arterial stiffness and hypertension status on diabetes onset [ 18 ]. The Framingham offspring cohort study found the relative contributions of arterial stiffness and hypertension to cardiovascular diseases [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies suggested that glycemic level and blood pressure interacted with arterial stiffness in patients with diabetes [15][16][17]. A recent study reported the predictive capacity of combined evaluation of arterial stiffness and hypertension status for diabetes onset [18]. However, the combined effect of arterial stiffness with glycemic control and hypertension status on macrovascular complication in the diabetic population is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing pulse wave conduction velocity, the elasticity of the artery is reduced and the degree of arteriosclerosis is higher. The normal range of Ba-PWV is defined as < 1400 cm/s, and atherosclerosis is defined by Ba-PWV ≥ 1400 cm/s [ 9 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The present study used Ba-PWV to assess atherosclerosis [ 2 , 6 8 ]. The normal range of Ba-PWV is commonly defined as < 1400 cm/s and atherosclerosis is defined by a Ba-PWV ≥ 1400 cm/s [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global prevalence of DFUs varies by region. In Iraq, the prevalence of diabetes mellitus in our country was 9.3% in 2015 according to statistics published on International Diabetes Federation [6]. One of the frequent complications of diabetes in impoverished nations, such as our "own country".…”
Section: Epidemiology Of Diabetic Footmentioning
confidence: 96%